Development of Procedures for Disassembly of Industrial Products in Python Environment - Maurizio Guadagno; Eleonora Innocenti; Lorenzo Berzi; Saverio Corsi; Massimo Delogu (Engineering Proceedings)
Circular Design methodology is essential for sustainable industrial practices. This study provides a methodology with a Python-based computational tool that optimizes industrial products’ disassembly sequences, focusing on Design for End of Life (DfEoL) and Design for Disassembly (DfD) to promote Circular Design. The tool creates disassembly precedence graphs and shows the best disassembly path for target components, facilitating material recovery and environmental sustainability. The tool was applied to a case study on an Axial Flux Permanent Magnet (AFPM) electric motor. The approach provides a flexible and open access solution for optimizing product design within a Circular Design framework.